The view from the ladies stand : 13th annual Tom Brock Lecture : NSW Leagues Club Sydney NSW : 15 September 2011 - Spillane, Debbie; Australian Society for Sport History. Tom Brock Bequest Committee ([Sydney] : Tom Brock Bequest Committee on behalf of the Australian Society for Sport History, 2012)
"The the past 50 years, the place of women in rugby league has changed. Debbie Spillane draws on her own experiences, describing how the women in her family introduced her to rugby league. She tells of her search for a gap in the male defences that blocked her path to involvement in the sport that dominated her childhood. In a career that has included newspaper reporting, songwriting, coaching and ultimately journalism, rugby league has always been a common thread. Reporting on rugby league and working for a football club have given Debbie a unique cantage point from which to view the collective behavior of rugby league towards women. Debbie also observes the behaviour of women in and around the sport. How have the ways in which women participate in, affect and influence rugby league have changed over the years? What lies ahead on those fronts, and for the game in general?"--Back cover.
Keywords: Spillane, Debbie; Women sportswriters -- Australia -- Biography; Women sportscasters -- Australia -- Biography; Rugby League football -- Australia -- History; Sports spectators -- Australia; Australian